TEACHER AND LEARNER KNOWLEDGE OF COVID- 19 AND ITS MITIGATION STRATEGIES IN SELECTED SECONDARY SCHOOLS IN KAPIRI- MPOSHI DISTRICT, ZAMBIA - Kabeta, Rachel; Chilinga, Givers; Sakakombe, Leonard (African Journal of Education and Practice, 2022)
Purpose: This study examined the knowledge of teachers and learners of COVID-19 and further determined their awareness levels of the mitigation measures that were put in place by the government of the Republic of Zambia in order to ensure a safe and conducive environment for teaching and learning amidst the COVID - 19 pandemic. Methodology: The study employed a descriptive cross-sectional survey design, both qualitative and quantitative data were collected using a questionnaire consisting of 34 items, and focus group discussions were also done. Ten schools were selected using simple random sampling from the urban and rural parts of the district, from which fifty (50) grade and fifty (50) 12 learners and one hundred ten (110) teachers, giving a grand total of 210, were selected through simple random sampling. SPSS version 22 was used to analyze the data to generate descriptive statistics and other measures. Both quantitative and qualitative data collection methods were used. Qualitative data was collected through face-to-face interviews and focus group discussions, while a questionnaire was used to collect quantitative data. The results were presented using frequencies and percentages. Further statistical independent (2 tailed) Mann- Whitney U- tests were carried out to show whether there were differences in the research variables. Findings: The findings revealed that the participants were knowledgeable about the COVID-19 pandemic with a percentage of between 98% and 67%. In particular, participants indicated that they knew the various COVID-19 symptoms, methods of how COVID-19 spread, and that there was no vaccine at the time of the study. Further, this study showed that the participants were aware of the majority of the mitigation measures that the government through the Ministry of Health and Ministry of General Education put in place to curb the spread of the corona virus with a percentage of 99.5% to 67.5 %. Notably, participants showed that they were aware of mitigation measures such as social distancing, closure of schools, alternative ways of learning like online learning, television and radio education channels and, in some cases, homeschooling. Results from the U-test suggest that there was homogeneity between the participants across the various socio-demographic factors in terms of their COVID-19 knowledge and mitigation measures. These findings were also confirmed through the information obtained qualitatively through face- to- face interviews and focus group discussions. Unique Contribution to Theory, Practice and Policy: The study contributes to literature by providing more insight on the importance of teachers and learners being knowledgeable about what COVID-19 is, how it spreads and the mitigation measures. This is because when people are knowledgeable and aware of something, it becomes easier to prevent and control its transmission. Knowledge is important in ensuring successful implementation of many programmes such as preventing and controlling the spread of a pandemic. This study recommends that schools through the Ministry of Education and Ministry of Health should come up with viable strategies and permanent plans that should be used during emergencies such as the COVID-19 by ensuring that supplies such as face masks, sanitizers and other accessories are always available. Cleanliness and washing hands and general hygiene should become part of the school cultures. Both the Ministry of Education and Health should enhance, maintain and continue their awareness and mitigation strategies on the Covid-19 pandemic. This study has been guided by the school adaptation model which comes from the perspective of Social Learning theory by Albert Bandura. According to Bandura (1997) school adaptation could be considered as the process in which students learn how to act in a way suited to a new environment. This theory guided this study and provided deeper understanding of the process of teaching and learning during the COVID-19 pandemic. It further gives insights on how both teachers and learners needed to adapt to the changing environment of learning and teaching amidst the corona virus pandemic